Developing a project scorecard to measure the performance of project management in relation to EFQM excellence model - Mathias Scheiblich; Mihaela Maftei; Vanessa Just; Michael Studeny (Amfiteatru Economic Journal, 2017)
Strategic company plans are more frequently realised in the form of strategic projects. Project portfolio management is new territory for a lot of companies, especially regarding the evaluation of strategic projects and the final financial and social results. The paper focuses on a pattern methodology for the measurement of project management performance and for projects prioritisation process. For this purpose, we analyse relevant pieces of literature in the field of project management, as well as other connected fields, like maturity and excellence models, balanced and project scorecard and performance measurement. As research methodology we develop a Project Scorecard that is derived from the Balanced Scorecard and the EFQM model. This is used to connect the strategic decision making process to the operational level of a project in terms of objectives and expectations, by determining a proper set of parameters that can measure each element's impact on the project overall success. Our research focuses on two main parameters, staff and project maturity. Testing this tool is done by reviewing a sum of human resources documents and various employee surveys. The results offer an overall interpretation and key of the Project Scorecard.
Keywords: M1; M5; O22; 330; balance scorecard; project scorecard; excellence models; project management performance; maturity model